Effects of Triphenylamine Units on the Electrochemical and Electrochromic Properties of Polymers Based on Carbazole-Thiophene Derivatives. Issue 3 (9th March 2018) - Hu, Bin; Li, Chunyang; Liu, Zengchen; Zhang, Xinlei; Mo, Minghui; Jin, Lin
Abstract : Carbazole, triphenylamine and thiophene derivatives have received great interest due to their outstanding electrochemical and electrochromic performance. In this study, four novel monomers based on carbazole-thiophene and triphenylamine derivatives (BTC-TPA, BTC-DMTPA, DTC-TPA and DTC-DMTPA) were synthesized and characterized. The obtained monomers could form corresponding polymer films on the surface of ITO/glass electrode by electropolymerization. Electrochemical properties and morphology of the polymer films were investigated. Spectroelectrochemical measurements demonstrated that the polymer films could exhibit multi-color electrochromism, especially for P(DTC-TPA) film, which could show four different colors(brown-green, blue gray, blue and purple black) at different redox states. Moreover, all the polymer films also possessed good optical contrast, reasonable switching time and coloration efficiency. These finding implied that the obtained polymer films could be considered as good candidates for the opto-electronic applications.